Analisis Sensitivitas Harga dan Loyalitas Konsumen terhadap Minyak Goreng Kemasan di Kota Serang (Studi Kasus pada Minyak Goreng Merek Filma, Sunco, dan Tropical) - Nurhidayat, Dimas; Mulyati, Sri; Setiawan, Johan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Cooking oil is a strategic food commodity part of the nine staples (basic necessities) that play an important role in the consumption of the Indonesian people. Price sensitivity and consumer loyalty are factors that need to be considered in the competition for branded packaged cooking oil. Packaged cooking oil brands circulating in the market have varying quality and prices so that consumers will be more flexible in choosing cooking oil. The purpose of this study is to analyze price sensitivity and consumer loyalty to packaged cooking oil of Filma, Sunco, and Tropical brands. The location of the research was determined purposively. The method of analysis of this research is quantitative descriptive. The sample used was 96 respondents with the criteria of housewives as research respondents. The Huisman method is used to analyze price sensitivity and the loyalty pyramid method to analyze the level of consumer loyalty. The results showed that consumers of Filma brand packaged cooking oil were more sensitive to price changes than Sunco and Topical brand packaged cooking oils; consumers of Filma brand packaged cooking oil have a lower level of loyalty, while loyalty to Sunco and Tropical brand packaged cooking oil is good.